2012
DOI: 10.4049/jimmunol.1102651
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Human FcRL4 and FcRL5 Are Receptors for IgA and IgG

Abstract: Fc Receptor-Like proteins are a family of cellular receptors homologous to FcγRI, and predominantly expressed by B cells. They function to co-stimulate or inhibit B cell receptor signaling through consensus ITAMs and ITIMs, however the extracellular ligands of these receptors remain unknown or controversial. In this study, we tested the ability of human FcRL proteins to bind immunoglobulins and found FcRL4 and FcRL5 to be bona fide Fc receptors. In cellular binding assays, FcRL4 bound efficiently to IgA and Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 31 publications
7
102
0
1
Order By: Relevance
“…To further investigate the roles of these src-kinase family members in FCRL4-mediated immune regulation, we took advantage of the recently reported IgA-binding activity of FCRL4 (30). We confirmed binding of heat-aggregated human IgA to the Burkitt's lymphoma BJAB cell line expressing FCRL4 (Fig.…”
Section: Binding Of Aggregated Iga To Cells Expressing Fcrl4mentioning
confidence: 56%
“…To further investigate the roles of these src-kinase family members in FCRL4-mediated immune regulation, we took advantage of the recently reported IgA-binding activity of FCRL4 (30). We confirmed binding of heat-aggregated human IgA to the Burkitt's lymphoma BJAB cell line expressing FCRL4 (Fig.…”
Section: Binding Of Aggregated Iga To Cells Expressing Fcrl4mentioning
confidence: 56%
“…Using a chimeric receptor containing the cytoplasmic tail of FCRL5, crosslinking FCRL5 and the BCR was shown to recruit SHP-1 to the two ITIM motifs of FCRL5, resulting in reduced BCR-induced calcium mobilization and protein tyrosine phos-phorylation (20). We and others reported that FCRL5 binds intact IgG via a complex mechanism (21,22), and therefore immune complexes may link FCRL5 to the BCR, potentially blocking B cell activation similarly to the inhibitory FcgRIIB. Potential activating functions were also proposed for FCRL5 (23), similarly to FCRL3 (24) and FCRL4 (25), suggesting dual regulatory capacities.…”
Section: T He Generation Of B Cell Memory Is An Important Component Omentioning
confidence: 94%
“…Very recent studies by the Colonna group identified that human FCRL4 and FCRL5 bind heat-aggregated IgA and IgG (19), but the endogenous ligands for other B-cell-expressed FCRLs, including mouse FCRL5, have yet to be elucidated. Notably, two additional members interact with MHC-like proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ig binding has been detected recently for two human members (19), antibodies do not appear to associate with other FCRL proteins. Intriguingly, two other representatives have been found to interact with MHC-like molecules (20,21).…”
mentioning
confidence: 99%